Assessing the Mediating Role of Safety Communication Between Safety Culture and Employees Safety Performance - Gehad Mohammed Ahmed Naji; Ahmad Shahrul Nizam Isha; Abdulsamad Alazzani; Muhammad Shoaib Saleem; Mohammed Alzoraiki (Frontiers Media S.A., 2022)
The main purpose of this research was to investigate the mediating role of safety communication (SCO) in the relationship between safety culture (SC) and safety performance (SP) amongst employees in the petrochemical industry. Safety communication methods not only enhance working conditions but also have a positive impact on employee's behaviors and attitudes toward safety leading toward reduced incidents in the workplace environment. A stratified sampling method was followed to collect data in the petrochemical industry in Malaysia. Structural equation modeling (SEM) was utilized to analyze the hypothesized model, using data from 320 participants. The findings reveal that safety communication partially mediates the association between safety culture and safety performance. Further, safety culture was found to have a significant and positive effect on safety performance. This -study makes a significant theoretical contribution by providing empirical evidence on the direct and indirect relationship between safety culture and safety performance in the petrochemical industry.